A COMPARATIVE CLASSIFICATION OF PRIMARY EDUCATION PROCESSES IN FOREIGN COUNTRIES AND UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This academic article provides a comprehensive comparative analysis of the primary education systems within various foreign nations and the Republic of Uzbekistan. The study focuses on identifying the structural, pedagogical, and methodological characteristics that define the initial stages of formal schooling across different educational landscapes. By examining the fundamental approaches to curriculum design, teacher-student interaction, and the integration of innovative technologies, the research highlights both the unique cultural nuances and the universal standards prevalent in modern primary education. Furthermore, the paper evaluates the effectiveness of recent reforms implemented in Uzbekistan’s primary sector in comparison with international benchmarks. The findings suggest that while Uzbekistan has made significant strides in aligning its national framework with global trends, there remains a critical need for further integration of student-centred learning strategies and advanced assessment techniques. This comparative classification serves as a theoretical foundation for future policy development and pedagogical enhancements aimed at improving the quality of basic education in the domestic context.